2020
DOI: 10.21203/rs.3.rs-20967/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Socia networkl support and harm reduction activities in a peer led pilot study, British Columbia, Canada

Abstract: Abstract Background: People who smoke drugs (PWSD) are at high risk of both infectious disease and overdose. Harm reduction activities organised by their peers in the community can reduce risk by providing education; safer smoking supplies, and facilitate access to other services. Peers also provide a network of people who provide social support to PWSD which may reinforce harm reducing behaviours. We evaluated the numbers of supportive network me… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…While the characteristics of people who consume drugs through non-injection routes of consumption have been described [23][24][25][26], less is known about the subpopulation of people who access SCS for oral, intranasal, or inhaled drug use. Recent evidence from a supervised consumption service in Canada demonstrated that program participants were predominantly Indigenous, male, and between the ages of 20-39 [17].…”
Section: Introductionmentioning
confidence: 99%
“…While the characteristics of people who consume drugs through non-injection routes of consumption have been described [23][24][25][26], less is known about the subpopulation of people who access SCS for oral, intranasal, or inhaled drug use. Recent evidence from a supervised consumption service in Canada demonstrated that program participants were predominantly Indigenous, male, and between the ages of 20-39 [17].…”
Section: Introductionmentioning
confidence: 99%